1995
DOI: 10.1002/neu.480280409
|View full text |Cite
|
Sign up to set email alerts
|

Expression of engrailed in an array of identified sensory neurons: Comparison with position, axonal arborization, and synaptic connectivity

Abstract: engrailed (en) is expressed in the posterior region of embryonic segments and appendages of the cockroach, Periplaneta americana. By 23% of embryogenesis En immunoreactivity is apparent in the dorsal half of the cercus, appendages of segment A11. By 40% of development, En staining is present in the dorsomedial half of the cercus. The nucleus of the medial filiform hair sensory neuron (M), born in this region, expresses en strongly. Staining is never seen in the lateral neuron (L). En is expressed in M as the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
(32 reference statements)
2
12
0
Order By: Relevance
“…We have seen that en -driven membranous GFP persists in neurons of 1 week old adults, and a quantitative study of en-lacZ expression in the adult antenna determined that levels of expression fall only to about 60% of their initial levels over the entire lifetime of the animal (Rogina and Helfand, 1997). In other, more long-lived, insects it has been shown that En protein is persistently expressed in the adult CNS and sensory neurons (Blagburn et al, 1995, Siegler et al, 2001). What is the role of the persistent En expression seen in adult sensory neurons?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have seen that en -driven membranous GFP persists in neurons of 1 week old adults, and a quantitative study of en-lacZ expression in the adult antenna determined that levels of expression fall only to about 60% of their initial levels over the entire lifetime of the animal (Rogina and Helfand, 1997). In other, more long-lived, insects it has been shown that En protein is persistently expressed in the adult CNS and sensory neurons (Blagburn et al, 1995, Siegler et al, 2001). What is the role of the persistent En expression seen in adult sensory neurons?…”
Section: Discussionmentioning
confidence: 99%
“…At a gross anatomical level, it is known that En expression in body segments and appendages of Drosophila persists into adulthood (Hama et al, 1990, Rogina and Helfand, 1997) and it has been observed in some sensory and central neurons of adult cockroaches and grasshoppers (Blagburn et al, 1995, Siegler et al, 2001). However, the extent and functions of this adult neuronal En expression are not known.…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons for exhibiting techniques for this classical preparation is that the cerci system has been and still is an active area of research in addressing questions of the development of neural circuitry as well as questions regarding synaptic repair and regeneration [26][27][28][29][30][31] . Either method of evoking activity in the cockroach ventral nerve cord can be used to examine the effects of pharmacological agents or insecticides on nervous system function.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that it is not. For technical reasons, the colocalization of Exd and En has not been possible, but visual comparison of the patterns of neuronal staining in the CNS (see Blagburn et al 1995) suggest that, although some neurons (such as the dorsal unpaired median neurons) express both, many others express only Exd or only En.…”
Section: Expression Of Ubx/abd-a In Subsets Of Neurons In the Cnsmentioning
confidence: 98%
“…En in cercal neurons might utilize this "widespread binding" mechanism and act alone, without co-factors to increase its selectivity. Of note, a gradient of En protein expression has been observed in cockroach cercal sensory neurons (Blagburn et al 1995;Marie et al 2000); if En indeed binds widely to multiple low affinity sites, the amount of this protein in a sensory neuron might affect its phenotype in a quantitatively graded manner.…”
Section: Expression Of Ubx/abd-a In Subsets Of Neurons In the Cnsmentioning
confidence: 98%